Perancangan Hazard Identification Risk Assessment and Risk Control (HIRARC) dan Implementasi Solusi pada Stasiun Kerja Lubang Kancing PT Bintang Permata Sejati - Niko Setiawan; Novenda Kartika Putrianto (Teknik Industri Universitas Ma Chung, 2021)
This paper discusses the case of PT Bintang Permata Sejati, a garment manufacturing company that faced multiple labor accidents at the buttonhole stations over a five-month period. The absence of occupational health and safety management practices within the company made it challenging to address these incidents, resulting in the temporary suspension of the production process and significant expenses for the corporation. To resolve this issue, the company employed the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) design, which involves analyzing and solving problems in three stages. By implementing solutions such as using iron gloves, duct tape insulation, cable ties, taking advantage of relaxation breaks, and changing chairs, the company successfully identified and addressed 17 problems related to people, materials, methods, machines, and the environment, of which 8 were low-risk, 3 were medium-risk, and 6 were high-risk. The cost of implementing these measures was significantly less than the profits earned by the company, highlighting the importance of maintaining an up-to-date HIRARC design and conducting research on its effectiveness. This case underscores the significance of occupational health and safety practices in reducing accidents and promoting employee welfare in manufacturing companies.